A Study to Investigate the Importance of Physical Facilities to Improve Teaching Learning Process at College Level in Tehsil Kotli Azad Kashmir - Saeed, Nauman; Sheema,; Kayani, Almas Ikram (Asian Journal of Contemporary Education, 2018)
The primary focus of the research was to investigate the importance of physical facilities to improve teaching learning process at college level in tehsil Kotli Azad Kashmir. It was descriptive study in nature. All teachers of public colleges of tehsil Kotli Azad Kashmir constituted population of the study. The study was delimited to public colleges of tehsil Kotli. Two post graduate colleges were selected for pilot testing process and these colleges were also included in final study. Consecutive sampling technique was used to draw the sample from population and 50% sample was selected randomly from the population. The data obtained was analyzed by using SPSS software. The study explore that physical facilities are essential for any effective teaching learning process. Findings of the study were that enough availability of physical facilities should improve any teaching learning process. The study recommends that; all basic and needed educational facilities such as furniture and buildings etc should be provided. College’s libraries must be updated according to the requirement of syllabus. College’s laboratories are equipped according to syllabus requirements. All required A.V aids should be provided.